On the scaling of air launch vehicles - Kafafy, Raed; Idres, Moumen; Aldheeb, M.; Omar, H. (2011)
The purpose of this paper is to introduce a set of scaling laws for the preliminary design of air launch vehicles. Scaling laws have been successfully used for the early stages of preliminary design of aerospace vehicles. A set of scaling laws for the preliminary design of air launch vehicle are derived from first principles. The scaling laws are then compared against a pseudodetailed air launch vehicle design model. The trends of vehicle design and performance parameters with payload mass reduction are investigated. In the paper, scaling laws of air launch vehicles based on first principles are introduced for the first time in the aerospace literature to the authors’ knowledge.